Rambutan syndrome - Senathirajah, Pathman; VStudios ([S.l.] : VStudios, 2007)
The rambutan syndrome is a common error committed in network marketing that is counter-productive and can be destructive to business. Joint Mr. Pathman as he teaches how to overcome the rambutan syndrome and turn your business and your team arround using a more dynamic, personal and effective approach
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing